Facilitating an early career transition pathway to community nursing: A Delphi Policy Study - Diane Chamberlain; Clare Harvey; Desley Hegney; Lily Tsai; Sandy Mclellan; Agnieszka Sobolewska; Elspeth Wood; Joyce Hendricks; Troy Wake (Wiley, 2020)
Abstract Aim To further develop and validate a new model of the early career transition pathway in the speciality of community nursing. Design Delphi policy approach, guided by a previous systematic review and semi‐structured interviews. Methods Four rounds of an expert panel (N = 19). Rounds one, two and four were questionnaires consisting of a combination of closed (Likert response) and open‐ended questions. Round three comprised of a focus group conducted using virtual meeting technology. Results The final model demonstrated reliable and valid measures. There were deficiencies in "pre‐entry"-where the marketing of community nursing was negligible and the support around orientation informal and minimal, mainly due to tight budgetary concerns. Community practice holds a whole new dimension for nurses transitioning from acute care as the concept of "knowing your community" took time and support-time to be accepted reciprocally and develop a sense of belonging to the community.